Evidence-based land conservation framework using multi-criteria acceptability analysis: A geospatial tool for strategic land conservation in the Gulf coast of the United States. (October 2022) - Samiappan, Sathishkumar; Shamaskin, Andrew; Liu, Jiangdong; Liang, Yong; Roberts, Jennifer; Sesser, Amanda L.; Westlake, Shannon M.; Linhoss, Anna; Evans, Kristine O.; Tirpak, John; Hopkins, Todd E.; Ashby, Steve; et al.
Abstract: Strategic land conservation investments that prioritize stakeholder priorities show promise for protection of ecological integrity and associated socioeconomic benefits of land conservation. However, despite many known benefits, decisions on where and what to conserve are often made without effective ecological and socioeconomic considerations. Ideally, multiple measurable attributes relevant to the ecological and socioeconomic priorities of stakeholders should be brought into an efficient, data-driven framework to evaluate areas of interest and help optimize decisions on conservation investments. Planners need to have access to a dynamic, web-based platform that assesses and compares conservation areas based on geospatial, science-based, and stakeholder-driven data. In this work, we provide a co-produced framework for a multi-criteria Conservation Prioritization Tool (CPT) that is based on available geospatial data reflecting stakeholder priorities for land conservation. The framework allows for flexible and hierarchical weighting of goals and data measures by the decision maker and allows for optimization of conservation decisions through a geospatial multi-criteria decision analysis (MCDA). Geospatial MCDA is a popular approach for evaluating decision alternatives in conservation problems, but the scarcity of functional tools that are widely accessible still limits their breadth of use. In this work, we describe the structure and creation of the CPT and demonstrate its application in the United States Gulf of Mexico coastal region, an area over 700, 000 km 2 in size. We designed and implemented a dynamic, cloud-based software tool that both considers and ranks user priorities and utilizes geospatial MCDA to evaluate areas of interest for land conservation. This tool improves the effectiveness and efficiency of land conservation actions by reducing the time needed to gather ecological evidence, increasing the transparency of decision processes, and encouraging inter-organizational partnerships. The versatile and open-access nature of the CPT broadens the availability of the geospatial MCDA methodology for conservation planners across large regions. We intentionally developed the CPT framework and procedures therein to be transferable and open-source to other objectives for any desired spatial geography. Highlights: Land conservation decisions are often driven by costs& willing sellers than by social-ecological priorities of stakeholders. A dynamic, web-based, and data-driven tool was developed to evaluate among proposed conservation areas. The user can customize the weighting of conservation priorities, or use MCDA for maximum flexibility. The Conservation Prioritization Tool provides a transparent, data-informed decision process.